The gut microbial composition in polycystic ovary syndrome with insulin resistance: findings from a normal‐weight population - Fangfang He; Yumei Li (BMC, 2021)
Abstract Background Limited studies have reported the relationship between intestinal flora dysbiosis and clinical characteristics in polycystic ovary syndrome (PCOS). However, the structure and characteristics of gut microbiota in PCOS have not been fully elucidated. Objective To analyze the composition of the Intestinal flora population in normal-weight women with PCOS and insulin resistance(IR) compared to PCOS alone and healthy women. Methods A total of 14 PCOS patients with insulin resistant(PCOS-IR) and 12 PCOS alone (PCOS-NIR), and 10 age- and body mass index-matched healthy control women (HC). BMI: 18.5-23.9 kg/m2. The bacterial 16 S rDNA V3-V4 fragment was amplified and sequenced. Then, the sequencing data were analyzed for species annotation, community diversity, and inter-group differences, to explore gut microbial characteristics of the subjects and their correlation with clinical parameters. Results No significant difference in diversity was observed between PCOA and sample cluster analysis among the three groups (Beta-diversity) and Alpha-diversity. The relative abundance of Rothia, Ruminococcus, and Enterococcus was significantly higher in the PCOS-IR group than in the other two groups (P < 0.05), while that of Prevotella was dramatically decreased (P < 0.05). The abundance of Enterococcus was positively correlated with waist circumference, hip circumference, diastolic blood pressure, and insulin resistance index. Meanwhile, Rothia abundance is positively associated with waist circumference and free fatty acids. Conclusions The gut microbial composition of PCOS patients with insulin resistance is different from that of PCOS alone and healthy women. The difference is correlated with the clinical characteristics of PCOS, with regards to insulin resistance, abdominal obesity, free fatty acids, and other indicators. PCOS-IR patients have an increased abundance of Enterococcus which potentially the intestinal environment of the host by enriching the metabolic pathways related to insulin resistance, causing the occurrence and development of PCOS.